Oceanapia magna Sponge Presents Dual Effect on the Gastrointestinal Motility of Rodents: In Vitro and In Vivo Assays - Pereira, Joedna Cavalcante; Figueiredo, Indyra Alencar Duarte; de Oliveira, Filipe Rodolfo Moreira Borges; Ferreira, Sarah Rebeca Dantas; Aires Moreno, Giulyane Targino; da Silva, Tania Maria Sarmento; Pinheiro, Ulisses dos Santos; Santos, Barbara Viviana de Oliveira; da Silva, Bagnólia Araújo; Cavalcante, Fabiana de Andrade (Frontiers in Pharmacology, 2020)
Oceanapia magna Santos-Neto, Nascimento, Cavalcanti & Pinheiro sponges are distributed across tropical worldwide seas. Some studies of marine products have shown interesting activities in smooth muscle models. Hence, we assessed the effect of the ethanolic extract of Oceanapia magna. (OC EtOH) on acute toxicity and gastrointestinal motility (in vitro and in vivo) in rodent models. On guinea pig ileum, OC EtOH induced a concentration dependent contraction on basal tonus, which was not inhibited by atropine, but in the presence of pyrilamine or verapamil, the effect was antagonized. Contrastingly, on KCl- or histamine-induced contractions, OC EtOH presented a transient contraction followed by a concentration dependent relaxation. Moreover, OC-EtOH presented a relaxant profile on cumulative curves to CaCl2 and tonic contraction induced by S ( ) BayK8644, through Cav blockade. The acute toxicity assay showed that OC EtOH (2000 mg/kg, p.o.) did not present any sign of toxicity in female mice. Additionally, OC-EtOH presented antidiarrheal effect in mice, increased the intestinal normal transit and reduced the castor oil-induced intestinal transit. Thus, OC-EtOH presented a dual effect on guinea pig ileum promoting contraction through activation of H1 and CaV, and relaxation through CaV blockade, besides the effect on upper gastrointestinal transit in mice, showing a potential medicinal use of this sponge in intestinal diseases such as diarrhea.